PENGARUH PEMERAMAN TERHADAP KUAT TEKAN TANAH LEMPUNG PATUMBAK DESA SUKA TENANG KABUPATEN DELI SERDANG YANG DISTABILISASI DENGAN ABU BATUBARA - Surta Ria Nurliana Panjaitan; Semangat Marudut Tua Debataraja (LPPM ISTP, 2025)
The Patumbak clay soil of Deli Serdang Regency from North Sumatra is a type of fine-grained soil with low bearing capacity and is sensitive to changes in water content so that the soil is unstable. This is very detrimental if clay is used as base soil to support building construction. So to overcome this problem it is necessary to stabilize clay soil as the base soil. One way is to add coal ash to clay soil. The research was carried out on clay soil from Patumbak, the Unconfined Compression Test value was 0.1702 kg/cm2. The tests carried out are preliminary tests to obtain the physical and mechanical properties of clay and clay soils that have been stabilized. Testing continued with the addition of coal ash and curing. The percentage of coal ash content used is 0, 5, 10, 15 and 20% and the curing variations used are 0, 1, 4, 7 and 14 days and then an Unconfined Compression Test is carried out to determine the compressive strength value using the optimum water content obtained in the compaction test. The results of the research show that curing and adding coal ash content to clay soil with optimum water content will increase the compressive strength value of the clay soil. The maximum Unconfined Compression Test value was obtained on a 20% coal ash mixture with a value of 0.6371 kg/cm2 at 14 days of curing. The results of the research can be concluded that curing and stabilization using coal ash on clay soil can sufficiently improve the physical and mechanical properties of the soil.